Analisis Banjir Di Sungai Ambawang Menggunakan Topography Wetness Index - Ajun Purwanto; Paiman Paiman (JURNAL SAINS INFORMASI GEOGRAFI, 2025)
Flood is one of the natural disasters that often occurs in Indonesia. Floods cause social, economic, health, and ecosystem impacts. This study aims to map flood-prone areas using the Topographic Wetness Index (TWI) approach and analyze its spatial characteristics in the Sungai Ambawang sub-district. The data used in this study is the Digital Elevation Model (DEM) from SRTM with a resolution of 30 meters. Based on the results of the analysis, it is known that the research area has three vulnerability classes, namely low, medium, and high. The low vulnerability class has a distribution area of 63,028.86 ha (61.42% of the total area), the medium vulnerability class has a distribution area of 37,931.2 ha (36.96%), and the high vulnerability class has a distribution area of 1,661.77 ha (1.62%). There needs to be an effort to anticipate and manage floods in Sungai Ambawang, which is prioritized in areas with medium and high vulnerability. Priority areas with moderate vulnerability are mostly spread across the villages of Sungai Ambawang Kuala, Mega Timur, Sungai Durian, Central Java, Korek, Pancaroba, Simpang Kanan, Puguk, Pasak, Lingga, Bengkarek, and Pasak Piang villages. The total area is 37,931.2 ha (37%). Areas with high vulnerability priority are mostly spread across the villages of Sungai Ambawang Kuala, Mega Timur, Sungai Durian, Central Java, Korek, Panca Roba, Simpang Kanan, Puguk, Pasak, Lingga, Bangkarek, Pasak Piang, and Teluk Bakung. The total area of this area is 1,661.77 ha (2%). Good spatial planning can reduce the occurrence of recurring flood disasters. The use of TWI in determining flood hazards effectively follows conditions in the field.